The visual exposure in forest and rural landscapes: An algorithm and a GIS tool - Domingo-Santos, Juan M.; de Villarán, Rubén Fernández; Rapp-Arrarás, Ígor; de Provens, Eva Corral-Pazos (Landscape and urban planning, 2011)
► GIS algorithm that quantifies visual exposure in solid angle units. ► Solid angle as a measure of covered surface area of a given object on the retina. ► Values of visual exposure can be used in modeling specific visibility of objects. ► Algorithm also providing cumulative visual exposure for multiple observation points. ► Useful tool in landscape planning, forest management, and visual impact assessment. There have been many different approaches to the delineation and measurement of viewsheds using GIS. However, the quantification of visibility for each element within the viewshed is estimated by imprecise procedures. This paper proposes a GIS tool which analyzes the visual exposure of a terrain from single or multiple observation points, starting from a digital elevation model (DEM). The proposed procedure yields higher precision values than the existing methods, because it directly obtains the solid angle of each visible cell within the DEM. The procedure is based on building a triangle network from a DEM in a regular square grid (RSG), thereby eliminating the need to calculate the slope and aspect, which are necessary steps of other procedures. The visual exposure values for each cell can be added in order to estimate the visual impact of landscape elements represented by a set of cells in the RSG. The development of the tool was oriented towards mitigating the landscape impact caused by forestry activities, in order to comply with certification schemes for Sustainable Forest Management. The tool proved to be useful in assessing alternatives for distributing clear-cutting areas so as to minimize visual impact, and can be applied to any other landscape impact assessment, such as road construction, quarrying, farming or any other land use change.